B-Z Oscillating Reactions catalyzed by a Tetraazamacrocyclic Nickel(II) Complex in the Pyruvic Acid-Sulfuric Acid System - Hu, Gang; Xu, Zhi-Qiang; Xie, Fu-Xing; Hu, Lin; Ni, Shi-Sheng (Asian Journal of Chemistry, 2010)
New Belousov-Zhabotinskii (B-Z) oscillating reactions catalyzed by a tetraazamacfoeyclic nickel(II) complex in the NaBrO3-pyruvic acid-sulfuric acid system were reported. The complex contains the unsaturated macrocyclic ligand 5,7,7,12,14,14-hexamethyl-1,4,8.11-tetraazacyclotetradeca- 4,11-diene. The influences of the cocentration of the component in the system and temperature on the oscillations were studied. The oscillation trajectories of the potentials of platinum electrode vs. those of bromide selective electrode are spirals but not limit cycles.